Linguistic issues in the development of ReGra: A grammar checker for Brazilian Portuguese - Martins, Ronaldo Teixeira; Hasegawa, Ricardo; Gracas Volpe Nunes, Maria Das; Montilha, Gisele [UNESP]; De Oliveira, Osvaldo Novais (Cambridge University Press (CUP), 1998)
This paper presents a number of linguistic and computational issues identified during the implementation of a general use grammar checker for contemporary Brazilian Portuguese, ReGra, that has been incorporated in the word processor REDATOR by Itautec/Philco (Brazil). Two main strategies were employed in the implementation of correction rules an error-driven, localist approach based on the identification of patterns indicative of grammatical mistakes and a more generic approach that requires automatic syntactic analysis. In this discussion, particular emphasis is given to the development of a parser based on a phrase structure grammar comprising over 600 production rules. As for the computational performance, ReGra permits texts to be revised at a rate of ca. 200 words per second. © 1998, Cambridge University Press. All rights reserved.